THE EFFECT OF SHARIA FINANCING ON COMPANY VALUE WITH PROFITABILITY AS A MODERATION VARIABLE IN SHARIA BANKING IN INDONESIA - Fazliati; Zulfan; Husaini; Wardhiah (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
This research is to look at the influence of Murabahah, Mudharabah and Musyarakah on Company Value with Profitability as a moderating variable in Indonesian sharia banking for the 2019-2022 period. This research data can be accessed on the official website www.ojk.co.id. The sampling technique in this research used purposive sampling to obtain 11 companies. The data analysis technique in this research uses Panel Data Regression and MRA methods with the Eviews 10 application tool. The research results found by researchers are that Murabahah has a positive and insignificant effect on company value (PBV), Mudharabah has a positive and insignificant effect on company value (PBV), Musyarakah has a positive and significant effect on company value (PBV). Profitability is unable to moderate Murabahah, Mudharabah and Musyarakah in Indonesian sharia banking for the 2019-2022 period.